Determination of Some Metals in Popcorn (Zea mays L.) Genotypes - Gokmen, Sabri; Tuzen, Mustafa; Mendil, Durali; Sari, Hayati; Hasdemir, Erdgogan (Asian Journal of Chemistry, 2016)
The study was conducted to determine some minerals in popcorn genotypes. Twenty genotypes, hybrid and open-pollinated, were evaluated for potassium, calcium, magnesium, sodium, copper, zinc, manganese and iron contents. The samples were analyzed by flame atomic absorption spectrometry. Contents of K, Ca, Mg and Na of the kernel of genotypes varied from 429-519, 45.8-126, 25.5-42.9 and 20.6-80.8 mg/kg, respectively while the ranges of trace elements were 1.73-11.89 for Cu, 39.0-63.0 for Zn, 13.7-46.5 for Mn and 57.9-112.0 mg/kg for Fe. In general, contents of trace elements tended to be higher in hybrids than open-pollinated populations.